Faktor Jantina dan Kepuasan Klien dalam Perkhidmatan E-Kaunseling - Zaida Nor Zainudin; Siti Aishah Hassan; Nor Aniza Ahmad; Yusni Mohamad Yusop; Wan Norhayati Wan Othman (USIM Press, 2024)
Vol. 6 No. 1 (2021): Jurnal Sains Insani